Ginger (Zingiber officinale Rosc.) germplasm evaluation for yield and quality in southern West Bengal - P K Chattopadhyay, S A Khan, T Chongtham, R Chatterjee, V Hnamte, (Journal of Spices and Aromatic Crops, 2013)
The experiment was conducted to assess ginger (Zingiber officinale) germplasm for yield and quality at Nadia (West Bengal). The experiment with 10 treatments was laid out in a Randomized Block Design with three replications. Ginger germplasm namely Suprabha, Suruchi, Suravi, V3S1-8, Himgiri, IISR Varada, IISR Mahima, IISR Rejatha, Gorubathan (local cv.) and Sambuk (local cv.) were selected for the study. The investigation indicated Gorubathan as the most promising germplasm in terms of growth and yield. The yield attributes like length of primary fingers (2.28 cm), diameter of secondary fingers (1.95 cm), rhizome yield plant-1 (0.201 kg) were highest with Gorubathan. The projected fresh yield was maximum (18.27 t ha-1) in Gorubathan but dry recovery was maximum with Sambuk (33.48%) and maximum oleoresin was with Suravi (10.25%).